PVA/Chitosan Hydrogel with Piper betle Extract: Waterproof Design, Exudate Management, and Antibacterial Efficacy Against Staphylococcus aureus & Escherichia coli - Manuppak Irianto Tampubolon; Natanael Priltius; Adiansyah Adiansyah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Injuries represent a major health concern in Indonesia, with the national health survey in 2022 reporting ~9% prevalence. In 2023, >146,000 traffic accident injuries and >370,000 occupational accidents were recorded, highlighting the urgent need for affordable and effective wound care solutions, particularly in underserved areas. Methods: Polyvinyl alcohol (PVA)–chitosan hydrogels were prepared via freeze–thaw crosslinking, incorporating Piper betle extract at 0.5%, 1%, and 2% w/w (F1–F3) alongside a control (F0). Physicochemical characterization included Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), swelling ratio, mechanical strength, water vapor transmission rate, and water resistance. Biological performance was assessed through antimicrobial testing (Staphylococcus aureus, Escherichia coli), fibroblast cytocompatibility assays, and in vitro release studies. Each assay was conducted in triplicate (n ≥ 3), and statistical analyses applied repeated-measures ANOVA or Friedman test (p < 0.05). Results: Hydrogels exhibited waterproof integrity and high exudate absorption (>400%), maintaining a moist wound environment. Antimicrobial assays showed clear inhibition zones (~15 mm) in Piper betle –loaded formulations, significantly greater than F0. Fibroblast viability exceeded 85%, confirming good cytocompatibility. In vitro release profiles demonstrated sustained bioactive release consistent with the Higuchi model. The combination of PVA–chitosan matrix and Piper betle extract produced hydrogels with stable physicochemical properties, controlled release kinetics, and potent antimicrobial activity, while remaining biocompatible.  Contributions: These findings support the potential of PVA–chitosan/Piper betle hydrogels as cost-effective wound dressings. Their clinical applicability is particularly relevant in rural and resource-limited healthcare settings in Indonesia, where the burden of injury and demand for accessible wound care products remain high